Innovation Through Green Paradox: An Antinomy of Green Marketing with Reference to Customers (Journal of Informatics Education and Research, 2024)
A global study commissioned by Nielsen found that 50 percent of customers can spend extra for business products and services that have introduced projects to contribute to society. There is a segment of consumers which are called “lifestyle of health and sustainability” (Solomon, M. R., & Lowrey, T. M., 2017). These consumers are those who want those products to be produced which are not harmful to the environment and are featured to be more sustainable in nature. Such customers create a market for green products and become a part of society that are taking apartment-friendly activities.This paper consists of the following key sections. The first segment starts with a summary of the principle of green Marketing. Marketing. First, the value of green messaging for businesses is outlined, along with the introduction of the most important standards for differentiating individuals concerning their environmental behavior, in the second section. After this contextualisation, the core methodological facets of study. The third segment of the inquiry applies to the investigation. The fourth segment of the article addresses the findings. The last segment addresses some functional consequences and draws some conclusions. Globally 58% of people worldwide posit that there is more of dejection when it comes to fighting climate change rather than hope for the same signalling that governments and change makers need to address a fundamental question:  How do consumers to not only care but act? Green needs to be made and sold attractive The objective of Green marketing is not causing any ill effect of industrial activities on the environment (Yan & Yazdanifard, 2014).